Social capital and project management success in a developing country environment: Mediating role of knowledge management. (3rd July 2021) - Amoako-Gyampah, Kwasi; Acquaah, Moses; Adaku, Ebenezer; Famiyeh, Samuel
ABSTRACT: Despite significant investments in projects by organizations, governments, and international development agencies in developing countries, many of the projects have failed and continue to fail due to budget overruns, inability to complete projects on time, and poor-quality outcomes. We draw on social capital theory and knowledge management to argue that individuals can leverage the resources embedded in the trust among other project participants, and the norms and values shared by the project participants and employees in an organization to enable them acquire, share and exploit knowledge for achieving project management success. Based on data collected from individuals engaged with projects in Ghana, this study tests a model in which knowledge management processes mediate the relationship between social capital and project management success. Our findings indicate that while trust is very important in the acquisition and sharing of knowledge, shared norms are very important in the sharing and exploitation of knowledge for project management success. Further, we find that the impact of norms and trust on project management success is mediated by knowledge sharing, and knowledge exploitation.